'Figurehead' hate crime cases: developing a framework for understanding and exposing the 'problem' with 'disability'. Issue 3 (4th May 2017) - Thorneycroft, Ryan; Asquith, Nicole L.
Abstract: The horrific stories of James Byrd Jr., Matthew Shepard and Stephen Lawrence are forever etched in criminal law. In each of these cases, activists, family members, politicians, academics, the public and media all reacted in their unique way to bring the problem of 'hate crime' onto the agenda. There are many other cases that have activated such a public imagination, or what we call 'figurehead' cases, yet the factors pertinent to figurehead recognition remain under-explored within hate crime scholarship. Using a case study analysis, three racist and heterosexist hate crime cases are examined in order to assess the individual and collective conditions that facilitated their place on the public agenda. This analysis has important implications for the category of 'disability', and highlights several shortcomings that forestall the recognition of 'disablist hate crime' publicly, legislatively and judicially. It is argued that the positioning of disability as 'abject' has inhibited the operationalization of disablist violence within the hate crime framework, and within criminal justice systems more generally.